Kemampuan Kerja dalam Mengelola Organisasi Pendidikan - Ahmad Ridwan (STAI ALHIKMAH Jakarta, 2015)
Abstract Leadership in an environment of educational organization for increasing teachers and staffs productivity to increase social services is one of factors influencing leader’s ability of work. The success of educational organization to get into top of achievement is often not followed by leader’s ability of work in managing his/ her educational organization. Such condition causes development decrease in that educational organization. The work ability of a leader can be observed from some stances, namely cognitive, emotional, physical, and intellectual ability. Keywords: Cooperation Ability, Educational Organization, Leader Abstrak Kepemimpinan di lingkungan organisasi pendidikan dalam meningkatkan produktivitas kerja tenaga pengajar dan karyawan dalam meningkatkan pelayanan kepada masyarakat menjadi salah satu faktor yang mempengaruhi kemampuan kerja pimpinan. Kesuksesan suatu organisasi pendidikan dalam mencapai puncak prestasi seringkali tidak diikuti dengan kemampuan kerja pimpinan dalam mengelola organisasi pendidikannya. Keadaan yang demikian itu mengakibatkan lambannya perkembangan lembaga pendidikan tersebut. Kemampuan kerja seorang pimpinan dapat dilihat dari beberapa sisi, diantaranya kemampuan kognitif (cognitif ability), kemampuan emosional (emotional ability), kemampuan fisik (phisical abilities), dan kemampuan intelektual (intelectual ability). Kata Kunci: Kemampuan kerjasama, Organisasi pendidikan, Pimpinan